Experimental investigation of small‐scaled model for powerhouse dam section on shaking table. Issue 5 (14th March 2012) - Chen, Jianyun; Wang, Mingming; Fan, Shuli
SUMMARY On the basis of the similitude law, Emulation Concrete, which meets the similitude requirements, was used for small‐scaled dam model test. For the dynamic failure mechanism of concrete gravity dam during earthquake to be studied, the dynamic model test on the shaking table was conducted for a powerhouse dam section. The reservoir and rigid foundation systems were considered in the test. The whole process of concrete gravity dam from elastic deformation, damage, to failure in various levels of Peak Ground Acceleration is studied through the tests. The failure mode of gravity dam is simulated, and the influencing factors are then analyzed by numerical method, which is based on concrete nonlinear elasto‐plastic model of damage mechanics. The analytical results are compared with experimental results. The damage patterns obtained from the numerical model are in good agreement with those obtained from shaking table tests including water reservoir effect and rigid foundation. Copyright © 2012 John Wiley & Sons, Ltd.